2022
DOI: 10.1098/rsob.210264
|View full text |Cite
|
Sign up to set email alerts
|

Mapping of a N-terminal α-helix domain required for human PINK1 stabilization, Serine228 autophosphorylation and activation in cells

Abstract: Autosomal recessive mutations in the PINK1 gene are causal for Parkinson's disease (PD). PINK1 encodes a mitochondrial localized protein kinase that is a master-regulator of mitochondrial quality control pathways. Structural studies to date have elaborated the mechanism of how mutations located within the kinase domain disrupt PINK1 function; however, the molecular mechanism of PINK1 mutations located upstream and downstream of the kinase domain is unknown. We have employed mutagenesis … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
35
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(47 citation statements)
references
References 43 publications
7
35
0
Order By: Relevance
“…In this pathway, depolarization of the inner mitochondrial membrane leads to an import arrest and stabilization of the mitochondrial kinase PINK1 at the outer mitochondrial membrane. PINK1 is then activated by autophosphorylation and phosphorylates ubiquitin and the ubiquitin‐like domain of the E3 ubiquitin ligase Parkin at serine 65, thereby activating Parkin (Gan et al , 2022; Kakade et al , 2022; Rasool et al , 2022; Sauve et al , 2022). Parkin‐mediated ubiquitination of outer membrane proteins recruits the autophagic machinery to eliminate damaged mitochondria.…”
Section: Resultsmentioning
confidence: 99%
“…In this pathway, depolarization of the inner mitochondrial membrane leads to an import arrest and stabilization of the mitochondrial kinase PINK1 at the outer mitochondrial membrane. PINK1 is then activated by autophosphorylation and phosphorylates ubiquitin and the ubiquitin‐like domain of the E3 ubiquitin ligase Parkin at serine 65, thereby activating Parkin (Gan et al , 2022; Kakade et al , 2022; Rasool et al , 2022; Sauve et al , 2022). Parkin‐mediated ubiquitination of outer membrane proteins recruits the autophagic machinery to eliminate damaged mitochondria.…”
Section: Resultsmentioning
confidence: 99%
“…This effect was not apparent upon transient expression of this mutant, confirming that overexpression of PINK1 is prone to mask such cryptic phenotypes. Interestingly, both Q115L and D525N are located just outside two α-helical regions in PINK1 that were recently shown to interact with each other and to be important for PINK1 activation in cells [ 43 ]. Several other changes in these regions presented additionally with reduced auto- and substrate phosphorylation, suggesting that intramolecular interaction between an N- and C-terminus of PINK1 are critical for its stabilization at the TOM complex [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…While some of these PINK1 N-MTS variants are still cleaved by PARL in healthy mitochondria and accumulate following mitochondrial damage (Sekine et al 2019), their import rates and effects on MPP processing remain unstudied. Experiments which swap the PINK1 N-MTS with those from other mitochondrial proteins have shown that PINK1 can still be imported into mitochondria with chimeric N-MTS’s, though PINK1 accumulation is prevented (Kakade et al 2022). While many of these N-MTS PINK1 chimeras can still be imported, their specific rates of import have also yet to be measured.…”
Section: Pink1 As a Case Studymentioning
confidence: 99%